Improving Predictions of the 3D Dynamic Model of the Plasmasphere - Pierrard, Viviane; Botek, Edith; Darrouzet, Fabien (Frontiers in Astronomy and Space Sciences, 2021)
In this perspective paper, we review and discuss different ways that can be used to improve the predictions of the models of the plasmaspheric region. The density of the background cold plasma and the plasmapause position are very important to determine for formation and propagation of waves and interactions with the other regions of the magnetosphere. Improvement of predictions includes refinement of forecast of the geomagnetic indices that influence the density and temperature of the particles in some models. Progress is also necessary in the understanding of the physical processes that affect the position of the plasmapause and its thickness since this boundary is not always very sharp, especially during low geomagnetic activity. These processes include the refilling after geomagnetic storms and substorms, the links with the ionosphere, and the expanding plasmaspheric wind during prolonged quiet periods. Using observations from in situ satellites like Van Allen Probes (EMFISIS and HOPE instruments), empirical relations can be determined to improve the dependence of the density and temperature as a function of the radial distance, the latitude and the magnetic local time, inside and outside the plasmasphere. This will be the first step for the improvement of our 3D dynamic SWIFF plasmaspheric model (SPM).